IMPLEMENTASI PROGRAM PENGEMBANGAN TEKNOLOGI PADI SALIBU DI KABUPATEN TANAH DATAR - Novira Rahmayuni; Hendri Koeswara; Roni Ekha Putera (Universitas Lambung Mangkurat, 2023)
This study aims to describe how the implementation of the Salibu Rice Cultivation Technology Development Program in Tanah Datar Regency. This research was motivated by a decrease in the area of rice harvested in West Sumatra in 2020. Tanah Datar Regency is the second largest district that experienced a decline in harvested area. In Tanah Datar Regency there is a program that aims to achieve food security known as the Salibu Rice Technology Development Program. This program can be one of the solutions related to the decline in harvested area that occurred in Tanah Datar Regency. But unfortunately the implementation of this program has not been implemented optimally. The formulation of the problem in this research is how to implement the Salibu Rice Technology Development Program in Tanah Datar Regency. The theory used in this study is the implementation theory by Van Meter and Van Horn which consists of six variables, namely: size and policy objectives, resources, inter-organizational relationships, characteristics of implementing agents, and sosial, economic and political conditions. This study uses a qualitative descriptive approach, data collection techniques used are interviews, observation and documentation. The selection of informants was carried out by purposive sampling technique and the data validity technique used was triangulation technique. The result of the research is that the implementation of the Salibu Rice Technology Development Program has been implemented but is not yet optimal. This is caused by several things, namely the absence of regulations at the level of a regent's regulation that regulates the implementation of this program, the lack of human resources in terms of quantity and non-human resources in terms of the budget, as well as an unsupportive sosial and economic environment.